Association between external eating and dietary patterns among middle school students in Chongqing, China - Deng, Yingjiao; Zhao, Lingxi; Guo, Linlu; Zhang, Yu; Lan, Yuanyuan; Mou, Youtao; Ran, Wenhua; Liu, Ling; Shi, Zumin; Zhao, Yong (Frontiers in Nutrition, 2025)
BackgroundThe dietary pattern, serving as a comprehensive indicator of the nutritional intake of middle school students, plays a crucial role in guiding their health. External eating, the behavior of eating based on external cues associated with food (e.g., the sight and smell of food), is a key factor influencing the choice of dietary patterns.ObjectiveTo investigate the dietary patterns of middle school students in Chongqing and analyze the association between external eating and dietary patterns.MethodsA cross-sectional study was conducted among 6,590 middle school students from 17 districts and counties in Chongqing, selected by stratified cluster sampling. The questionnaire included basic information about the participants, external eating score [based on the Dutch Eating Behaviour Questionnaire (DEBQ)] and dietary frequency, and data were collected via online self-report. Exploratory factor analysis was employed to extract dietary patterns, and multiple linear regression analysis was used to analyze the association between external eating and dietary patterns among middle school students.ResultsThe total score for external eating among middle school students in Chongqing ranges from 19 to 27. Three dietary patterns were identified among middle school students: modern dietary pattern, fast-food dietary pattern, and balanced dietary pattern. The results of multiple linear regression analysis showed that, external eating is positively associated with fast-food and balanced dietary pattern after adjusting for confounders [β = 0.006, 95% confidence interval (CI) : (0.002, 0.011), P = 0.002; β = 0.005, 95% CI: (0.001, 0.010), P = 0.016], external eating was negatively associated with modern dietary pattern [β = –0.005, 95% CI: (–0.009, –0.001), P = 0.018].ConclusionExternal eating exhibits a significant negative association with modern dietary pattern among middle school students. Therefore, middle school students should be guided to correctly deal with external eating, so as to establish a reasonable dietary pattern.